Task oriented training for Stroke Rehabilitation: A mini review - Ayesha Afridi; Arshad Nawaz Malik; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2023)
Stroke is the leading global cause of death and disability and the need for stroke rehabilitation services in increasing. The usual stroke rehabilitation protocol involves a combination of therapeutic exercises, occupational therapy, speech therapy and counselling sessions depending upon the severity of the deficit and associated co-morbidities. However, there is a need for better protocols and new therapies for improving outcomes after stroke rehabilitation. The term ’task-oriented training’ (TOT) refers to guided rehabilitation training of patients’ limb function using goal oriented tasks, which can be used to enhance neuroplasticity in brain after injury. Task oriented training could be modified with action selection and environmental enrichment to fulfill the limitations of stroke like, holistic approach, outcome/goal based intervention, proper dosage for desirable outcomes. This mini review provides an overview of the TOT and to identify gaps and challenges in stroke rehabilitation related to integrating TOT. Keywords: Stroke, Rehabilitation, holistic approach, task oriented training.